Recursive parameter estimation algorithms - Coelho, J.P. (2010)
Main adaptive control design approaches assume that a suitable dynamic model of the controlled process can be computed. In this way, recursive parameter estimation algorithms play can important role in tracking the time variant parameters of the process dynamic model. Thois paper describes the major algorithms used to compute the ttransfer function parameters of time varying ssssystems. The advantages and limitations of these techniques are illustrated by computing the parameters of a time varying discrete system, with known structure, under the presence of persistent and non-persistent information.